Post-PISA Education Reforms in China: Policy Response Beyond the Digital Governance of PISA. (September 2019) - Yang, Wenjie; Fan, Guorui
Purpose: This study analyzes the Programme for International Student Assessment (PISA) data, revealing that the test itself reflects China's educational problems as well as the resultant effect of digital governance. Examining the root cause of these problems, this study demonstrates that the education reforms implemented in response to the PISA have gone beyond digital governance. Design/Approach/Methods: This study conducts a text analysis of materials related to China's education system, including PISA data and analytical reports published by the Organisation for Economic Co-operation and Development since 2009. Findings: Reflected by PISA data, the main problems facing China's educational sector include the overburdening of students at school, emphasis on knowledge acquisition during the teaching process, and the prevalence of extracurricular tuition. The digital governance effect triggered by PISA is highly consistent with China's constant and excessive pursuit of efficiency, emphasis on scores, and the rate of students entering higher level schools. In the new era, China actively reflected on the disadvantages of digital governance before implementing a series of education reforms that go beyond it. Originality/Value: This study is based on China's cultural background and the latest contexts. It examines the impact of the large-scale international assessment on China's education governance and discusses the impact of digital governance on the education reforms in other countries. The implementation of China's post-PISA education reforms demonstrates that different countries can implement rational education reforms based on their own cultural traditions and social realities as well as by referencing and using PISA data with care and prudence.